Implementation of Cigarette Excise Policy against Cigarette Consumption Reduction among Adolescent in Kuningan, Indonesia - Ramjani, Jani; Rahim, Fitri Kurnia; Amalia, Icca Stella; Putra, Wahyu Manggala (Kesmas, 2017)
Indonesia has the highest prevalence of smoking (50.68%) compared to other ASEAN countries. On January 1st, 2017, the Indonesian government raised cigarette excise taxes. The purpose of this study was to analysis the impact of cigarette excise increase on cigarette consumption among adolescents aged 17 to 25 years. The study design used cross-sectional survey. A total of 153 adolescents were recruited in this study through simple random sampling technique. Questionnaires and observation papers were used in this study. A face-to-face interview was conducted to fulfill the data collection through home visit for each respondent. The data were obtained during May – June 2017. This study used paired t test analysis. The number of cigarettes consumed by adolescent decreased significantly by two cigarettes per day after the increase in cigarette excise tax. There is a significant difference of the average cigarettes price based on the brand after the implementation of cigarette excise tax increase, the difference of cigarette price is IDR 200 per stick of cigarettes after excise tax increase. Increased cigarette excise taxes may affect the increasing of cigarette prices. Threfore, it could reduce the number of cigarette consumption.